Innovative Web Framework for Cervical Cancer Detection: A Machine Learning Advancement - Mittapalli Murali,; S. Prathap,; B. Ramana Reddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This research presents an innovative web framework designed specifically for detecting cervical cancer using sophisticated machine learning methods. By utilizing an extensive dataset that includes information on demographics, medical history, sexual behavior, contraceptive use, and prior medical diagnoses, our framework integrates several models: AdaBoost, XGBoost, a stacking classifier, and logistic regression. These models work together to improve both the accuracy and dependability of diagnoses. The primary goal of the framework is to facilitate early detection and intervention, which are vital for enhancing patient outcomes in cervical cancer treatment. Through a detailed evaluation and comparison of these algorithms, our study highlights their effectiveness in predictive modeling for cervical cancer, representing a notable advancement in applying machine learning to healthcare.
Keywords: AdaBoost; XGBoost; Stacking Classifier; Logistic Regression Models